Association of AXIN1 rs12921862 C/A and rs1805105 G/A and CTSB rs12898 G/A polymorphisms with papillary thyroid carcinoma: A case–control study - Saljooghi, Shaghayegh; Heidari, Zahra; Saravani, Mohsen; Rezaei, Mahnaz; Salimi, Saeedeh (Journal of clinical laboratory analysis, 2023)
Background Papillary thyroid cancer (PTC) is the most common type of thyroid cancer which its precise etiology remains unknown. However, environmental and genetic factors contribute to the etiology of PTC. Axis inhibition protein 1 (Axin1) is a scaffold protein that exerts its role as a tumor suppressor. In addition, Cathepsin B (Ctsb) is a cysteine protease with higher expression in several types of tumors. Therefore, the aim of this study was to investigate the possible association of AXIN1 rs12921862 C/A and rs1805105 G/A and CTSB rs12898 G/A polymorphisms with PTC susceptibility. Materials & Methods In total, 156 PTC patients and 158 sex‐, age‐, and BMI‐matched control subjects were enrolled in the study. AXIN1 rs12921862 C/A and rs1805105 G/A and CTSB rs12898 G/A polymorphisms were genotyped using the PCR–RFLP method. Results There was a relationship between AXIN1 rs12921862 C/A polymorphism and an increased risk of PTC in all genetic models except the overdominant model. The AXIN1 rs1805105 G/A polymorphism was associated with an increased PTC risk only in codominant and overdominant models. The frequency of AXIN1 Ars12921862 Ars1805105 haplotype was higher in the PTC group and also this haplotype was associated with an increased risk of PTC. Moreover, the AXIN1 rs12921862 C/A polymorphism was not associated with PTC clinical and pathological findings, but AXIN1 rs1805105 G/A polymorphism was associated with almost three folds of larger tumor size (≥1 cm). There was no association between CTSB rs12898 G/A polymorphism and PTC and its findings. Conclusion The AXIN1 rs12921862 C/A and rs1805105 G/A polymorphisms were associated with PTC. AXIN1 rs1805105 G/A polymorphism was associated with higher tumor size. Papillary thyroid cancer (PTC) is the most common type of thyroid cancer which genetic and environmental factors play key roles in its pathogenesis. Axin1 is a scaffold protein which plays a tumor suppressor role. Cathepsin B is a cysteine protease enzyme with higher expression in tumors. Regarding the role of Axin1 and Cathepsin B on tumorigenesis, the aim of this study was to evaluate the effect of Axin1 and Cathepsin B polymorphisms on PTC. The AXIN1 rs12921862 and rs1805105 polymorphisms was associated with increased risk of PTC. The AXIN1 rs1805105 polymorphism was associated with larger tumor size (≥1 cm). There was no association between CTSB rs12898 polymorphism and PTC.